Giving Combination of Alkaline Water and Organic Calcium Sources Towards Liver Health Indicators in Broiler Chicken - Mawan Pasaribu; Vitus Dwi Yunianto; Fajar Wahyono; Bambang Sukamto; Lilik Krismiyanto (Bantara Journal of Animal Science, 2020)
The purpose of this study was to determine the liver health in broiler chickens which were fed with additional organic calcium sources combined with alkaline water. The material used was 240 broilers with an average body weight of 195.25 ± 6.85 g. The study used a completely randomized design with a 2x3 factorial pattern, the first factor was 3 levels of alkaline water, namely 0% (A1), 10 mL (A2) and 20 mL. (A3), and the second factor is 2 levels of organic calcium sources, namely eggshell flour (B1) and shellfish (B2). Each treatment was repeated 4 times, each filled with 7 heads. Parameters measured were serum glutamate okasaloacetate transminase (SGOT), serum glutamate pyruvate transminase (SGPT) and relative liver weight. The results showed that the combination of alkaline water and organic calcium sources showed an interaction with SGOT, while the relative weight of the liver and SGPT had no interaction. The conclusion is that the combination of alkaline water levels up to 20 mL and organic calcium sources (eggshell and shellfish flour) is not harmful to broiler liver.Keywords: alkaline water, broiler chickens, liver indicators and sources of calcium